Effect of gallium and antimony impurity atoms on the photoelectric properties of silicon - Bobir O. Isakov (Genius Journals, 2023)
In this work, the photoelectric properties of a silicon sample doped in series with Ga and Sb impurity atoms were studied. The shift of light towards the infrared region of silicon containing GaSb binary compounds was demonstrated experimentally. The result of the experiment was explained by the fact that Ga and Sb impurity atoms form GaSb binary compounds in local regions of the silicon crystal lattice at a certain temperature (600 °C). A 2D crystal lattice of the GaSb binary compound formed in the local region of the silicon crystal lattice was presented. The obtained experimental results require in-depth research on the formation of not only Ga and Sb, but also III-V binary compounds in the silicon crystal lattice.
Keywords: Silicon; gallium; antimony